Penerapan Metode PAIKEM Pada Pembelajaran Bahasa Jawa di Madrasah Ibtidaiyah Kelas Rendah - Siti Zuliana; Sinta Hardianti; Yulia Afida Damayanti; Muhammad Fikri Abdun Nasir (Jurnal Riset Madrasah Ibtidaiyah, 2023)
This study will discuss the application of the PAIKEM method to learning Javanese in lower grades. This type of research is qualitative research using a qualitative descriptive approach. Research data were obtained through observation and interviews conducted directly at MI NU Manafi'ul Ulum 01 Gebog Kudus. The results of research conducted at MI NU Manafi'ul Ulum 01 Gebog show that the application of the PAIKEM method to learning Javanese in low grades has a positive impact on students. In the application of the PAIKEM method at MI NU Manafi'ul Ulum 01 Gebog Kudus, Javanese language learning is carried out through three stages, namely the first stage of planning, in the planning process for the PAIKEM method it is explained that the teacher plans and implements teaching and learning activities that motivate students to play an active role in their education. In the second stage, namely implementation, the PAIKEM method is carried out by implementing learning by stimulating active, innovative, creative, effective and fun learning. Through the use of this method, learning Javanese is very effective, to be applied to lower grades in MI/SD because applying this method can make students more active, not bored, and excited during the learning process.